Different opinions of ulama in Fiqh Waqf: Epistemological, methodological, and contextual analysis - Ridwansah, Asep Ahmad; Solehudin, Ending (UIN Sunan Gunung Djati Bandung, 2025)
This study critically examines juristic disagreement (ikhtilaf) in waqf jurisprudence through an integrated epistemological, methodological, and contextual analysis, while exploring the pathways toward harmonizing classical doctrines with contemporary socio-economic demands. Using a qualitative, library-based research design, the study analyzes classical fiqh sources from the four Sunni schools, foundational works of uṣūl al-fiqh, contemporary academic discussions, and modern fatwas. The research scope encompasses the conceptual foundations of waqf, the validity of various asset types, istibdal, temporary waqf, and contemporary innovations, including cash waqf, waqf-linked sukuk, and digital waqf. The findings reveal that ikhtilaf is rooted in divergent epistemic commitments regarding textual authority, legal causation, and public interest, as well as methodological distinctions in legal reasoning and contextual influences across historical periods. Major challenges include the increasing complexity of financial instruments, fragmented regulatory frameworks, and limited capacity among waqf managers to operationalize maqasid-oriented governance. The study recommends strengthening collective ijtihad, developing maqasid-driven regulatory frameworks, and establishing measurable evaluative standards for modern waqf practices. Practical implications highlight the need to integrate classical fiqh reasoning with contemporary governance principles to ensure that waqf remains socially transformative and aligned with sustainable development objectives. This research formulates a normative–analytical model that synthesizes maqasid-oriented reasoning with juristic diversity, providing a conceptual platform for harmonizing waqf jurisprudence and enhancing the strategic relevance of waqf in the modern era.